A framework for developing and supporting student leadership in higher education. Issue 1 (2nd January 2020) - Skalicky, Jane; Warr Pedersen, Kristin; van der Meer, Jacques; Fuglsang, Sally; Dawson, Phillip; Stewart, Sarah
ABSTRACT: Developing leadership in students is part of the remit of higher education institutions. In recent decades, student leadership development programs have proliferated at universities worldwide. However, the contested understanding of the term 'leadership' has resulted in lack of clarity regarding how this may be 'developed' in higher education. There are many programs that contribute towards developing leadership in students and not all of them do so explicitly. Moreover, in the absence of clear conceptual underpinnings and pedagogic approaches, it is questionable whether these programs can deliver the graduate capabilities employers are increasingly expecting. Recognising this diversity and range of different understandings of leadership that underpin these programs, this paper presents an overarching inclusive framework that provides guidelines to support quality assurance across the broad range of leadership development initiatives in higher education. The paper describes the development of the framework, explains its core components and provides an illustration of it.